Assessment of knowledge about rabies in interns of Geetanjali medical college, Udaipur - Mishra, Neeta; Solanki, Shiv Lal (International Journal Of Community Medicine And Public Health, 2017)
Background: Rabies is one of the zoonotic diseases. Dogs are the main reservoir of Rabies in India but it can cause by any rabid carnivores bite. The untreated, improperly treated or neglected cases lead to sure death. Rabies can be prevented through proper management by vaccination, serum and immunoglobulin but once disease occurred it is always fatal. Objectives: To assess the knowledge regarding rabies and its preventive measures among the interns. Methods:It was a cross-sectional study conducted in January 2014 to March 2014. Data was collected using preformed questionnaire from 100 interns of Geetanjali medical college, Udaipur. Results:It was seen that only 59% knew that vaccination of dogs was an essential preventive measure, 80% and 68% agreed that pre-exposure vaccination and educating the people regarding pre- and post-exposure prophylaxis were useful, respectively. Also 89% and 59% were aware that wound should be washed immediately and antiseptics should be applied, respectively. 50% and 29% were not aware of the schedule and dose of the PEP, respectively. Only 35% knew about both IM and ID route of administration of PEP. Only 66% were aware that the site of administration of PEP is deltoid. Conclusions:The study showed that there was lack of proper knowledge in interns about the prevention and management of rabies which needs to be proper training and proper education.